Development of nanoscale drug delivery systems of dihydroartemisinin for cancer therapy: A review - Ka Hong Wong; Donglin Yang; Shanshan Chen; Chengwei He; Meiwan Chen (Elsevier, 2022)
Dihydroartemisinin (DHA), a first-line antimalarial drug, has demonstrated great anticancer effects in many types of tumors, including liver cancer, glioblastoma, and pancreatic cancer. Due to its abilities to induce programmed cell death (PCD; apoptosis, autophagy and ferroptosis), inhibit tumor metastasis and angiogenesis, and modulate the tumor microenvironment, DHA could become an antineoplastic agent in the foreseeable future. However, the therapeutic efficacy of DHA is compromised owing to its inherent disadvantages, including poor stability, low aqueous solubility, and short plasma half-life. To overcome these drawbacks, nanoscale drug delivery systems (NDDSs), such as polymeric nanoparticles (NPs), liposomes, and metal-organic frameworks (MOFs), have been introduced to maximize the therapeutic efficacy of DHA in either single-drug or multidrug therapy. Based on the beneficial properties of NDDSs, including enhanced stability and solubility of the drug, prolonged circulation time and selective accumulation in tumors, the outcomes of DHA-loaded NDDSs for cancer therapy are significantly improved compared to those of free DHA. This review first summarizes the current understanding of the anticancer mechanisms of DHA and then provides an overview of DHA-including nanomedicines, aiming to provide inspiration for further application of DHA as an anticancer drug.